2002
DOI: 10.1080/15419060214523
|View full text |Cite
|
Sign up to set email alerts
|

Local Cell Membrane Deformations due to Receptor-Ligand Bonding as Seen by Reflection Microscopy

Abstract: Understanding surface receptor clustering and redistribution processes at the cell-matrix contact zone requires detailed knowledge of the spatial integration of these molecules in the architecture of this complex interface. Here we present and discuss critically a procedure to extract such information combining reflection contrast microscopy (RCM) and reflection interference microscopy (RIM). As model system, we used living human umbilical vein endothelial cells (HUVEC) adhering to laminin-coated surfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This work identifies the interaction collagen XXIII and integrin ␣ 2 ␤ 1 by solid phase and surface plasmon resonance spectroscopy and describes their co-localization on the surface of basal keratinocytes in mouse skin at the microscopic level. In addition, we show at the ultrastructural level that collagen XXIII is localized in nondesmosomal areas of the keratinocyte membrane, a localization also suggested for integrin ␣ 2 ␤ 1 (44).…”
Section: Discussionsupporting
confidence: 73%
“…This work identifies the interaction collagen XXIII and integrin ␣ 2 ␤ 1 by solid phase and surface plasmon resonance spectroscopy and describes their co-localization on the surface of basal keratinocytes in mouse skin at the microscopic level. In addition, we show at the ultrastructural level that collagen XXIII is localized in nondesmosomal areas of the keratinocyte membrane, a localization also suggested for integrin ␣ 2 ␤ 1 (44).…”
Section: Discussionsupporting
confidence: 73%
“…In recent investigations we labeled many diVerent proteins using the method of SDS freeze-fracture cytochemistry (Peskan et al 2000;Galle et al 2002;Pop et al 2003;Sherameti et al 2004;Westermann and Rhiel 2005). We made the experience that white or bright appearing replica areas with thin or even no platinum deposition (platinum shadows) show equal or higher labeling eYciencies than regions consisting of mixed Pt/C.…”
Section: Resultsmentioning
confidence: 98%
“…Galle et al . () studied the contact zones of endothelial cells adhering to laminin‐coated surfaces. They found that RCM permitted the determination of the lateral position of the marked receptor molecules, to an accuracy of about 100–200 nm.…”
Section: Resolution Of Rcmmentioning
confidence: 99%